Rapid and Complete Remission of Metastatic Adrenocortical Carcinoma Persisting 10 Years After Treatment With Mitotane Monotherapy: Case Report and Review of the Literature. Issue 13 (March 2016) - Ghorayeb, Nada El; Rondeau, Geneviève; Latour, Mathieu; Cohade, Christian; Olney, Harold; Lacroix, André; Perrotte, Paul; Sabourin, Alexis; Mazzuco, Tania L; Bourdeau, Isabelle
Abstract : Abstract: Mitotane has been used for more than 5 decades as therapy for adrenocortical carcinoma (ACC). However its mechanism of action and the extent of tumor response remain incompletely understood. To date no cases of rapid and complete remission of metastatic ACC with mitotane monotherapy has been reported. A 52-year-old French Canadian man presented with metastatic disease 2 years following a right adrenalectomy for stage III nonsecreting ACC. He was started on mitotane which was well tolerated despite rapid escalation of the dose. The patient course was exceptional as he responded to mitotane monotherapy after only few months of treatment. Initiation of chemotherapy was not needed and he remained disease-free with good quality of life on low maintenance dose of mitotane during the following 10 years. A germline heterozygous TP53 exon 4 polymorphism c.215C>G (p. Pro72Arg) was found. Immunohistochemical stainings for IGF-2 and cytoplasmic β-catenin were positive. Advanced ACC is an aggressive disease with poor prognosis and the current therapeutic options remain limited. These findings suggest that mitotane is a good option for the treatment of metastatic ACC and might result in rapid complete remission in selected patients.